MANAGEMENT OF STRATEGIC DEVELOPMENT OF TRANSPORT INFRASTRUCTURE OF THE NATIONAL ECONOMY - БОНДАР, ЮЛІЯ; Hutsaliuk, Oleksii (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article considers the issues of strategic development management, which are a prerequisite and at the same time a tool for long-term development of transport infrastructure enterprises. Systematic and comprehensive development of the term «strategic development management» occurs through a consistent combination of developments of scientists and business representatives. After all, modern views and knowledge on the management of strategic development in the current socio-economic conditions significantly affect the effectiveness of the strategic management system and the development of transport infrastructure enterprises. Despite the large number of scientific studies on the strategic management of the enterprise, the issues of managing the strategic development of the transport infrastructure enterprise remain unclear. Therefore, there is a need for further in-depth study of theoretical and methodological developments in the management of strategic development of the enterprise, formulation of the strategic planning process, quantitative concepts, approaches and methods, choice of strategies, provision and implementation of developed plans. The aim of the article is to study modern features and substantiate the theoretical basis of management of strategic development of transport infrastructure. The impact on transport infrastructure enterprises of the current economic situation in the country, globalization of economic changes, characterized by a high degree of uncertainty and risk is observed. The essence of the concept of strategic development management of the transport infrastructure enterprise is investigated. The concept aims at preparing the available resources and opportunities that open up in the future, by applying a detailed strategic analysis and developing strategic plans in order to improve the efficiency of the enterprise through timely response and quick adaptation to unpredictable environmental changes and services provided. Thus, there is a need for further study of the application of strategic development management in transport infrastructure enterprises, which will characterize the economic, organizational, technical capabilities of production and their maximum use, timely coordination of business plans for enterprise development.